1986
DOI: 10.1128/mcb.6.8.2766
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional role for the nontranscribed spacer of rat ribosomal DNA.

Abstract: In vitro transcription of the rat rRNA gene led to the identification of a region within a 3.4-kilobase fragment of the nontranscribed spacer (NTS) which significantly increased the transcription of rat ribosomal DNA. Promoter constructs containing this region were transcribed up to 17-fold more efficiently in vitro than templates with only 167 or 286 base pairs of NTS. This effect was also observed when the 3.4-kb fragment of the NTS was subcloned in the opposite orientation and 4 kb upstream of the promoter.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 30 publications
0
42
0
Order By: Relevance
“…Transcription assays were done essentially as described previously (4). To examine the effect of NBP (pl6) on the transcription of rDNA, we preincubated the templates with purified p16 for 5 min before adding extract.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Transcription assays were done essentially as described previously (4). To examine the effect of NBP (pl6) on the transcription of rDNA, we preincubated the templates with purified p16 for 5 min before adding extract.…”
Section: Methodsmentioning
confidence: 99%
“…The spacer or NTS promoter (5,21,40,46), which is much weaker than the 45S (or 40S in Xenopus species) gene promoter, may also play a role in regulating rRNA synthesis. In addition, enhancer elements (4,7,8,27) have been identified at various distances upstream of the transcription initiation sites of the respective genes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…27 It has been suggested that these repeat sequences in Drosophila, Daphnia, Rattus, and Xenopus play a role in transcription enhancement of rDNA units. [28][29][30][31][32] The specificity of the repetitive DNA found within the intergenic spacer of the rRNA cistron is perhaps important for the development of specific probes for other species of the subgenus Nyssorhynchus.…”
Section: Discussionmentioning
confidence: 99%